Didactical Situations of Students’ Mathematical Reasoning Based on the Learning Obstacle on Quadrilateral Areas - Alawiyah, Ana; Budi Waluya, St.; Priyono Budi Prasetyo, Andreas (Unnes Journal of Mathematics Education Research, 2018)
This study aimed to: (1) identify some learning obstacles experienced by students related to the topic of rectangular areas, (2) find out the didactical design of mathematical reasoning to develop a didactical situation, (3) describe the didactical situation of mathematical reasoning in learning process, and (4) increase mathematical reasoning ability through the learning of didactical design. The method employed in this study was a qualitative method with Didactical Design Research (DDR) approaches consisting of three formal stages. The results showed that (1) there were four types of learning obstacles experienced by students about the concept of quadrilateral area, (2) the didactical design that has been prepared facilitated the students construct the area of quadrilateral through the triangle areas approach, (3) the didactical situation developed consisted of 12 didactical situations along with predictions of student’s responses and anticipation, (4) students’ learning obstacle could be minimized and students’ mathematical reasoning abilities had been increased. Thus, it could be concluded that the didactical design of mathematical reasoning could be used as a guideline for educators to design a didactical situation in mathematics learning activities.